Tourism intelligence in the Cabo Ortegal UNESCO Global Geopark: Case of San Andrés de Teixido - Sergio Muíño Freire; Begoña Muíño Sar (International Journal of Geoheritage and Parks, 2025)
Smart tourism planning and management emerges as a fundamental pillar for the sustainable development of tourist destinations. In this context, the aim of this research is to deepen the knowledge of tourism in the Cabo Ortegal UNESCO Global Geopark, specifically in relation to the profile of visitors, tourism demand and the potential for implementing a tourism intelligence network in the territory. The methodology used for its achievement is mixed, as it employs quantitative and qualitative techniques, using surveys, in-depth interviews, applications of digital tools, and a content study. The results are a novel and original contribution to the territory with the identification of the visitors' profiles of San Andrés de Teixido and their behaviour within the geopark. In turn, the creation of a data collection model for the tourist office of Cedeira allows to iniciate a network of intelligence and knowledge between the municipalities of the geopark.